2010
DOI: 10.1200/jco.2009.25.2627
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Coronary Artery Disease by Computed Tomography Angiography in Patients Treated for Childhood Hodgkin's Lymphoma

Abstract: PURPOSE To detect pathologies in coronary arteries by computed tomography angiography (CTA) in survivors of childhood Hodgkin's lymphoma who have been treated with radiotherapy and/or cardiotoxic agents. PATIENTS AND METHODS Patients with HL who have been in remission for at least 2 years after completion of therapy were included. CBC, lipid profile, urine analysis, brain natriuretic peptide, troponin-T, creatinine kinase-myocardial band, ECG, telecardiography, echocardiography, and CTA of the patients were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 40 publications
0
60
1
4
Order By: Relevance
“…40 Prospective screening studies among HL survivors demonstrate that clinically significant cardiovascular abnormalities, like coronary artery stenosis, coronary artery calcifications, reduced left ventricular dimensions, VHD, and conduction defects, are very common, even in asymptomatic survivors. [45][46][47][48] Large cohort studies of HL survivors show a two-to sevenfold increased risk of cardiac death (mainly myocardial infarction [MI]), depending on the age of the patients (stronger risk increases for radiotherapy at younger ages), treatment regimens used, and followup time. 2,5,49,50 Furthermore, three-to sixfold increased SIRs of CHD, VHD, and HF are observed in patients treated for HL relative to the general population, also after long-term follow up.…”
Section: Risk Of Cvdmentioning
confidence: 99%
“…40 Prospective screening studies among HL survivors demonstrate that clinically significant cardiovascular abnormalities, like coronary artery stenosis, coronary artery calcifications, reduced left ventricular dimensions, VHD, and conduction defects, are very common, even in asymptomatic survivors. [45][46][47][48] Large cohort studies of HL survivors show a two-to sevenfold increased risk of cardiac death (mainly myocardial infarction [MI]), depending on the age of the patients (stronger risk increases for radiotherapy at younger ages), treatment regimens used, and followup time. 2,5,49,50 Furthermore, three-to sixfold increased SIRs of CHD, VHD, and HF are observed in patients treated for HL relative to the general population, also after long-term follow up.…”
Section: Risk Of Cvdmentioning
confidence: 99%
“…Classical CAD risk factors (hypertension, diabetes, cigarette smoking, and hyperlipidemia) continue to play a role in promoting atherosclerosis in HL survivors, necessitating optimal medical management. [63] At present, there have only been two prospective studies of cardiac screening in HL survivors. Heidenreich et al [64] reported an abnormal stress test (echocardiogram and/or radionucleotide myocardial perfusion scan) in 21% of asymptomatic HL survivors fifty percent of those with an abnormal functional study demonstrated an obstructive lesion at the time of definitive coronary angiography.…”
Section: Cardiovascular Toxicitiesmentioning
confidence: 99%
“…5,6 These events, together with an inactive lifestyle 9,10 and tobacco use, 11 are secondary to cancer treatment c o m p l i c a t i o n s ( a n t h r a c y c l i n e chemotherapy regimen, 7 thoracic and cranial radiotherapy). 8,9 Although cancer survivors have a higher risk for late cardiometabolic events, they are mostly sedentary, frequently use tobacco and alcohol, [12][13][14] even since adolescence, 15 and do not attend periodic medical check-ups. 16 In Argentina, the annual incidence of childhood cancer is 124/1 000 000 in children younger than 15 years old, with an average survival of 65%.…”
Section: Introductionmentioning
confidence: 99%